Association between phase angle of bioelectrical impedance analysis and nutritional parameters in older adults - Santos, Mylena Alves; Goes, Andrea Costa; Oliveira, Rafaela de Siqueira; Oliveira, Juliana de Souza; Ferreira, Andrêa Jacqueline Fortes; Santiago, Emanuelle Cruz da Silva; Roriz, Anna Karla Carneiro; Oliveira, Carolina Cunha de (ABCS Health Sciences, 2023)
Introduction: Phase angle (PhA) is a Bioelectrical impedance analysis (BIA) parameter representing an indicator of cellular health and has been suggested as a biomarker of nutritional status. Objective: To evaluate the association between PhA and nutritional parameters in older adults. Methods: A cross-sectional study was conducted with community-dwelling older adults. Body mass index (BMI), arm muscle circumference (AMC), calf circumference (CC), body fat percentage (BF%), appendicular skeletal muscle mass (ASMM), serum albumin, mini-nutritional assessment (MNA), and PhA were assessed. Kolmogorov–Smirnov test, Spearman's correlation coefficient, chi-square test, and Poisson regression models were performed. Results: 144 participants were included in the study, and most of them were female, aged ≥80 years, and underweight. Most older adults with lower PhA were women, aged range 80–89 years, and with reduced ASMM (p<0.05). PhA presented a significant correlation with age (r=–0.417; p<0.001), ASMM (r=0.427; p<0.001), AMC (r=0.195; p=0.019) and BF% (r=–0.223; p=0.007). Older adults with lower PhA present reduced ASMM (PR: 1.25; 95%CI: 1.04–1.50), and hypoalbuminemia (PR: 1.50; 95%CI: 1.11–2.03). Conclusion: PhA is related to commonly nutritional indicators used in clinical practice and could be an important biomarker of muscle mass reserves in community-living older adults of both sexes.